Effect of glutamine supplementation against soybean meal-induced growth retardation, hepatic metabolomics and transcriptome alterations in hybrid sturgeon Acipenser baerii♀× A. schrenckii ♂ - Huamei Yue; Jinping Wu; Peng Fu; Rui Ruan; Huan Ye; Bin Hu; Xihua Chen; Chuangju Li (Aquaculture Reports, 2022)
This study aimed to evaluate the effects of glutamine supplementation to soybean meal (SBM) diet in hybrid sturgeon (25.00 ± 1.00 g). Three diets, including fishmeal (FM) diet, SBM diet, and SBMG diet (glutamine addition to SBM diet), were formulated to feed sturgeons for 8 weeks. Growth parameters and muscular crude lipid content were reduced by SBM substitution, and were further increased in SBMG-diet group. In liver morphology detection, moderate lipid droplets accumulation in hepatocytes found in fish fed SBM diet were partially retrieved by glutamine addition. Hepatic gas chromatography–mass spectrometry analysis detected 156 up-regulated metabolites and 15 related KEGG pathways affected by SBM replacement. Glutamine addition resulted in 102 down-regulated metabolites, together with 9 KEGG pathways enriched. In liver transcriptome sequencing analysis, 1074 and 1564 differentially expressed unigenes (DEGs) were detected by SBM/FM and SBMG/SBM pairwise comparisons, respectively. The least number of DEGs (143) was present in pairwise comparison of SBMG /FM. Our results indicated that glutamine addition attenuated the SBM-based negative effect including growth retardation, and muscle proximate composition alteration. Glutamine supplementation alleviated the liver damage caused by SBM substitution possibly through down regulating the elevated levels of metabolites or gene as well as related metabolic pathways.